Sensor Data-Driven Personalised Hip and Knee Replacement Rehabilitation Compared to Standard of Care, Pilot Randomized Trial - McNamara, I; Whitehouse, C. E; Ward, N; Hodgins, Diana; Whalley, R (British Journal of Healthcare and Medical Research, 2023)
This pilot was to evaluate if GaitSmart, a sensor based digital health rehabilitation solution, could be administered in a clinical setting, and compare patient outcomes of GaitSmart directed rehabilitation with Standard of Care (SoC) for patients after lower limb arthroplasty. The intervention group were monitored 4 times, 3 weeks apart, with GaitSmart, starting at least 6 weeks after surgery and compared to a SoC group, treated in accordance with NICE Guidelines. Each group contained sub-groups comprised of 14 hip and 8 knee patients, total 44 participants. Gait speed increased by a clinically significant amount of 0.16 m/s in both hip and knee intervention groups, compared to 0.04m/s and -0.01m/s in the hip and knee SoC groups. Hip and knee intervention compared to hip and knee SoC; Total joint angles increased by 9.9° and 11.4° compared to 5.0° and 1.4, Utility Score of the EQ5D-5L increased 0.05 and 0.01 compared to 0.13 and 0.10 and the EQ5D-5L VAS score increased by 9 and 3.7 compared to 3.6 and 5.3. For the Oxford Hip Score, the intervention group increased by 3.5 and the SoC group by 6. For the Oxford Knee Score the intervention group increased by 7.4 and the SoC group by 4.3. Patients in the intervention and SoC groups increased confidence in walking 45% and 16% respectively. The study demonstrates the GaitSmart intervention programme can be administered in outpatients with high patient satisfaction and provides clinically meaningful results for the primary outcome gait speed.